The effect of advertisements on premature customer readiness stages for NMSB product / Ashmir Arfendy Johari Wee (Faculty of Business Management, 2006)
Neural Manufacturing Sdn Bhd is a subsidiaries of Neural Groups which it main activities is manufactured new technologies in biometric security systems. In ensuring the awareness of the customer towards their product, the company has used three approaches in the advertisement field to communicate with their customer. The purpose of this research is to identify which of these approaches is efficient and effective to increase the awareness of the customer towards the company products. This research involved 60 respondents, which is the existing customer of the company itself. The respondent has been choosing randomly. Questionnaires have been distributed in order to obtain the information from the respondent. In finding and interpretation of the data, three methods have been used. This includes frequency to know quantity of respondents frequently gain for given factors, cross tabulation method is used in order to know the correlation between one factors to another factors, and last method used was kendall tau-b and kendall tau-c to test the hypothesis of the relationship between the advertisement approaches and the premature customer readiness stages or in other words, customer awareness accordingly.